Antithrombotic Effect of Human Recombinant Tissue Factor Pathway Inhibitor on Endotoxin-induced Intravascular Coagulation in Rats: Concerted Effect with Antithrombin - Kamikubo, Yu-ichi; Hamuro, Tsutomu; Matsuda, Jun-ichi; Shinya, Noriko; Miyamoto, Seiji; Funatsu, Akinobu; Kato, Hisao (Thrombosis and Haemostasis, 1996)
In our current study, we examined the antithrombotic effect of Chinese hamster ovary cell-derived human recombinant tissue factor pathway inhibitor (h-rTFPI) by intravenous injection of h-rTFPI with or without antithrombin into endotoxin-treated rats. An injection of h-rTFPI at a high dose (4 mg/kg of h-rTFPI or three doses of 1 mg/kg) significantly prevented the decrease of fibrinogen and factor VIII and the increase of fibrin/fibrinogen degradation products and glutamic-pyruvic transaminase in rats, while a single injection of 1 mg/kg of h-rTFPI or 250 U/kg of antithrombin did not significantly prevent intravascular coagulation. However, a simultaneous injection of 1 mg/kg of h-rTFPI and 250 U/kg of antithrombin did significantly prevent intravascular coagulation. From the studies on the clearance rate and immunohistochemical staining of injected h-rTFPI into normal rats, we found that most of the intravenously-injected h-rTFPI was localized on the central vein and sinusoids in the liver and catabolized via the proteoglycan-mediated pathway with a half-life of 48 min. These results suggest that h-rTFPI and antithrombin prevented endotoxin-induced intravascular coagulation in concert by binding to the vascular walls of the liver and by inhibiting fibrin formation on Kupffer cells in hepatic sinusoids.